IMPROVEMENT OF THE METHOD OF INCREASE THE INTERRUPTION RESISTANCE OF THE SIGNALS DETECTION SYSTEMS OF THE MEANS OF COVERT INFORMATION COLLECTION - Laptiev, Oleksandr; Savchenko, Vitalii; Kopytko, Serhii; Ponomarenko, Vitaliy; Parkhomenko, Ivan (Ukrainian Information Security Research Journal, 2023)
In the process of detection and recognition of signals of random signals, which can be signals of digital means of covert information acquisition, an urgent issue is the improvement of immunity. The article examines the features of using low-pass filters. Low-pass filters with quadratic and linear dependence of the response on the input signal. The principle of operation of filters is that the process of summation is performed. At the same time, the useful signal is summarized coherently, and the interference signal is summed up incoherently. The useful signal increases and the interference signal decreases. When a rectangular pulse is applied to the input of the linear and quadratic filters, which imitates the signals of modern digital means of covert information acquisition, the parameters of the output signals necessary for further use are determined: mathematical expectation, correlation coefficient, dispersion, root mean square deviation, ratio of values signals to the amount of interference in temporal and spectral view. Calculated winning ratio. This coefficient shows the efficiency of using low-pass filters. Graphs of the envelope voltage at the output of an ideal bandpass filter when a rectangular pulse of different duration is applied to the input– a signal that can be a signal of covert information acquisition means. Modeling of the filtering process with different correlation coefficients was carried out. The simulation results confirmed the possibility of identifying the signal of means of covert information acquisition by the method of determining the two-dimensional probability density of the interference signal against the background of the general signal. The process of improving the immunity of the system as a whole is being studied. The improvement of the signal detection method was carried out due to the use of low-frequency narrow-band filters in the process of signal processing, which allows to achieve a 23% increase in the immunity of the system for identifying and recognizing signals of digital means of covert information acquisition.